Activity‐specific metabolic rates for diving, transiting, and resting at sea can be estimated from time–activity budgets in free‐ranging marine mammals. Issue 9 (23rd March 2017) - Jeanniard‐du‐Dot, Tiphaine; Trites, Andrew W.; Arnould, John P. Y.; Speakman, John R.; Guinet, Christophe
Abstract: Time and energy are the two most important currencies in animal bioenergetics. How much time animals spend engaged in different activities with specific energetic costs ultimately defines their likelihood of surviving and successfully reproducing. However, it is extremely difficult to determine the energetic costs of independent activities for free‐ranging animals. In this study, we developed a new method to calculate activity‐specific metabolic rates, and applied it to female fur seals. We attached biologgers (that recorded GPS locations, depth profiles, and triaxial acceleration) to 12 northern ( Callorhinus ursinus ) and 13 Antarctic fur seals ( Arctocephalus gazella ), and used a hierarchical decision tree algorithm to determine time allocation between diving, transiting, resting, and performing slow movements at the surface (grooming, etc.). We concomitantly measured the total energy expenditure using the doubly‐labelled water method. We used a general least‐square model to establish the relationship between time–activity budgets and the total energy spent by each individual during their foraging trip to predict activity‐specific metabolic rates. Results show that both species allocated similar time to diving ( 29%), transiting to and from their foraging grounds ( 26–30%), and resting ( 8–11%). However, Antarctic fur seals spent significantly more time grooming and moving slowly at the surface than northern fur seals (36% vs. 29%). Diving was the most expensive activity ( 30 MJ/day if done non‐stop for 24 hr), followed by transiting at the surface ( 21 MJ/day). Interestingly, metabolic rates were similar between species while on land or while slowly moving at the surface ( 13 MJ/day). Overall, the average field metabolic rate was 20 MJ/day (for all activities combined). The method we developed to calculate activity‐specific metabolic rates can be applied to terrestrial and marine species to determine the energetic costs of daily activities, as well as to predict the energetic consequences for animals forced to change their time allocations in response to environmental shifts. Abstract : Knowledge of energy costs associated with different daily activities of free‐ranging animals is a stepping stone to physiological, behavioral, and ecological studies, and yet is yet very difficult to determine in the wild. We developed a method to estimate activity‐specific metabolic rates in free‐ranging fur seals based on fine‐scale time–activity budgets derived from biologging data. Our results show that diving is more expensive than transiting at the surface or grooming in free‐ranging fur seals which is in accordance with previously reported measures. The method developed in this study could be applied to other species to determine cost of daily activities in wild marine or terrestrial animals.